ASSESSMENT OF THE RUSSIAN FEDERATION REQUIREMENT IN POTENT ANALGESICS - A. V. Sosnov; S. S. Golubev; B. S. Punkevich; S. V. Sadovnikov; F. M. Semchenko; V. N. Tohmahchi; A. A. Sosnova (Разработка и регистрация лекарственных средств)
According to comparative analysis of medical consumption of potent analgesics in economically developed countries was justified the need to increase production of active ingredients of potent analgesics in Russia by more than ten times. Also a list of the most relevant analgesics for production for chronic patients and for use in emergency situations was provided. It was shown that the production of substances of potent analgesics in Russia by 2020 should be increased up to 5-6 tons in morphine equivalent. This amount takes into account the need to expand diversity of dosage forms suitable for patient, including transdermal, transmucosal, intranasal, and others. The proportion of natural and semi-synthetic opioid analgesics should be at least 50% of the total production in morphine equivalent. Use of genetically modified varieties of opium poppy allows to obtain the raw material with a predetermined content of target alkaloids. It is proposed to organize production of active analgesics ingredients at one of repurposed military facilities, as well as recreate biotechnological production of raw materials on the basis of genetically modified varieties of poppy. This approach allows to produce active analgesics ingredients for all pharmaceutical manufacturers of Russian Federation. It is proposed to organize production of certified reference materials of significant pharmaceutical drugs and psychotropic substances for all Russian consumers - more than 250 licensed organizations in industry, health care, law enforcement, chemical safety and security.